2017
DOI: 10.1103/physrevd.95.036005
|View full text |Cite
|
Sign up to set email alerts
|

Extending chiral perturbation theory with an isosinglet scalar

Abstract: We augment the chiral Lagrangian by an isosinglet scalar and compute the one-loop radiative corrections to the pion mass and decay constant, as well as the scalar mass. The calculations are carried out for different patterns of chiral symmetry breaking of immediate relevance for phenomenology and lattice investigations. By construction our results encompass several interesting limits, ranging from the dilaton to the linear sigma model.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 70 publications
1
67
0
Order By: Relevance
“…While looking for explanations, so far without results, it is natural to raise the question if the quality of the data set can really differentiate between dilaton and σ-model scenarios. The more robust general test yielded an exponent y close to y = 2 which perhaps could be accommodated in some generalized effective action of the σ-model with added terms and with loop corrections [31,32]. This is illustrated next with the conventional fitting procedure in chiral perturbation theory.…”
Section: Tests Of the Asymptotic Dilaton Potential V(χ) ∼ χ Pmentioning
confidence: 87%
“…While looking for explanations, so far without results, it is natural to raise the question if the quality of the data set can really differentiate between dilaton and σ-model scenarios. The more robust general test yielded an exponent y close to y = 2 which perhaps could be accommodated in some generalized effective action of the σ-model with added terms and with loop corrections [31,32]. This is illustrated next with the conventional fitting procedure in chiral perturbation theory.…”
Section: Tests Of the Asymptotic Dilaton Potential V(χ) ∼ χ Pmentioning
confidence: 87%
“…For SU(3) with R ¼ F and N f ¼ 8, as is evident in Table II, there is a significant difference between the values of our two Padé approximants, indicating that a calculation of the series to higher order in Δ f than OðΔ 4 f Þ would be desirable. This theory with N f ¼ 8 has been the subject of a number of lattice studies, including [58,59] (see also [60,61]), which have observed quasiconformal behavior. This behavior is consistent with the inference that for SU(3) and R ¼ F, the value N f ¼ 8 is close to, but slightly less than, N f;cr , in agreement with our estimate in Eq.…”
Section: ð3:17þmentioning
confidence: 99%
“…Recently there has been renewed interest in effective field theories (efts) featuring the dilaton degree of freedom [24][25][26][28][29][30][31][32][33]. Going further away from the conformal window, we expect the dilaton state to merge into the lightest scalar state of the theory loosing its conformal properties, as properly encoded in the agnostic effective approach of [32]. This interest in the dilaton state is due to lattice studies of SU (3) gauge theories with matter field content consisting of N f = 8 fundamental Dirac fermions [34][35][36][37], and N f = 3 symmetric 2-index Dirac fermions (sextet) [38][39][40] known as Minimal Walking Technicolor [11,24,25,41].…”
mentioning
confidence: 99%